2016
DOI: 10.1116/1.4971171
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer etching of SiO2 by alternating an O2 plasma with fluorocarbon film deposition

Abstract: This work demonstrated a process for the atomic-scale etching of SiO2 films, consisting of alternating nanometer-thick fluorocarbon film deposition with O2 plasma irradiation in a capacitively coupled plasma reactor. Ar plasma etching after fluorocarbon film deposition tends to suffer from nanometer- or subnanometer-thick carbon films deposited on the SiO2 surface and chamber walls. These carbon films cause various problems, such as reductions in the etching rate per cycle and degradation of the SiO2 quality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…During Ar + bombardment, the FC layer is transformed from a layer rich in CF 2 and CF 3 into one with a majority of F-deficient CF and C-(CF x )F y . This is in good agreement with previously published ALE SiO 2 studies [4,23,24,35]. In addition, some residual F bound mostly to Si is present in the near surface region, as seen in the F(1s) spectra in figure 10(b).…”
Section: Ar + Ion Bombardment Of Fluorocarbon-dosed Surfacessupporting
confidence: 92%
See 1 more Smart Citation
“…During Ar + bombardment, the FC layer is transformed from a layer rich in CF 2 and CF 3 into one with a majority of F-deficient CF and C-(CF x )F y . This is in good agreement with previously published ALE SiO 2 studies [4,23,24,35]. In addition, some residual F bound mostly to Si is present in the near surface region, as seen in the F(1s) spectra in figure 10(b).…”
Section: Ar + Ion Bombardment Of Fluorocarbon-dosed Surfacessupporting
confidence: 92%
“…Tsutsumi et al developed an ALE SiO 2 process where O 2 plasma irradiation was used as the modified layer removal step, following fluorocarbon film deposition. They successfully suppressed a carbon-rich residual film while removing a consistent amount of SiO 2 per cycle [35].…”
Section: Ar + Ion Bombardment Of Fluorocarbon-dosed Surfacesmentioning
confidence: 99%
“…This layer can then be etched using Ar or O 2 plasma at low ion energy bombardment 2,3,[6][7][8][9][10][11] . However, some drifts were reported in the processes, with an increase of the etch amount per cycle (EPC) due to the fluorine contamination of the reactor walls [8][9][10]12 . Yet, Dallorto et al have shown that the effect of fluorine from the reactor wall contamination is reduced by decreasing the substrate temperature to − 10 °C and below 12 .…”
mentioning
confidence: 99%
“…Other methods for surface preparation for EBSD analysis are chemical polishing [5][6][7][8], electropolishing [9] or ion milling [10]. Plasma etching [11][12][13] is one of the methods applied for the etching of polymers [14], single crystal diamond [15], SiO 2 layers [16], carbon [17] or Ti-Al 3 Ti laminates [18]. Usually, low-pressure plasma etching requires costly vacuum equipment [14].…”
Section: Introductionmentioning
confidence: 99%